A Package of Time-Shared Computer Programs for Patient Care - Jelliffe, Roger W. (1977)
A collection of time-shared computer programs for patient care has been developed. It contains programs for clinical pharmacology to analyse dosage requirements of digitalis glycosides, kanamycin, gentamicin, streptomycin, cephaloridine, procainamide, lidocaine, and six inhalation anesthetics. Programs for cardiology analyse data from the cardiac catheter laboratory, from echocardiograms, and from systolic time intervals. Those for the pulmonary function laboratory analyse data of blood gases, spirometry, lung volumes, and diffusing capacity. Other programs compute endogneous creatinine clearance for adults and for newborn infants without requiring collection of the usual urine specimen, and others aid in decision analysis, application of Bayes' theorem, and in computing a fever index. The collection can be used over internationally accessible time-sharing facilities.